Correlações estruturais entre rochas de Cráton São Luís (Mina Aurizona) e Oeste Africano - RODRIGUES NETO, José Maria dos Santos (2018)
The correlation between the São Luís Craton and the West African Craton has been discussed based mostly om petrological, geochronological and geochemical criteria, which indicate a possible genetic connection between the rocks of the two continents. Structural analysis of both contexts performed in this work sought to corroborate that interpretation under the aspect of Strucutral Geology. The rocks of São Luís Craton are composed by supracrustal metavulcanossdimentary rocks of the Rhyacian period (Aurizona Group) intruded by granitoids (Tromaí Intrusive Suite). The craton is limited to the south by the Gurupi Belt, which is assumed to have been formed through an oblique collision system with mass transport from SW to NE during the Neoproterozoic. The rocks of Aurizona Group display ENE-WSW regional trend, as demonstrated by ductile-brittle shear zones frequently associated to hydrothermal gold deposits, exemplified by Aurizona Gold Mine (analysed in detail on this work). A second NE-SW trend of sinistral structures is exhibited crosscutting the main trend. In paleogeographic terms, Aurizona Group is correlated to Baoulé-Mossi Domain in the West African Craton. The domain is composed by rhyacian greenstone belts with NE-SW regional trend, as exhibited by NE-SW ductile-brittle shear zones formed during the Eburnean Orogeny. A second and later N-S trend is also noted, usually marked by sinistral shear zones. These structures are the main control for hydrothermal gold deposits in the region. The structural arrangement of the two cratons are compatible, except for the current trend which differ in approximately 25º. However, this deviation may be explained through the clockwise rotation of the south american continent of similar angle after its separation from the African Continent in the Gondwana break-up. The correlation’s plausible results indicate that São Luís Craton is actually a cratonic fragment of the West African Craton, and that both share an origin in the Rhyacian period as, well as deformation during the Eburnean Orogeny. Moreover, it is indicated that Aurizona Group may in fact be characterized as a greenstone belt terrain.